Expanding the cerebrospinal fluid endopeptidome. Issue 5 (March 2017) - Hansson, Karl T.; Skillbäck, Tobias; Pernevik, Elin; Kern, Silke; Portelius, Erik; Höglund, Kina; Brinkmalm, Gunnar; Holmén‐Larsson, Jessica; Blennow, Kaj; Zetterberg, Henrik; Gobom, Johan
Abstract : Biomarkers of neurodegenerative disorders are needed to assist in diagnosis, to monitor disease progression and therapeutic interventions, and to provide insight into disease mechanisms. One route to identify such biomarkers is by proteomic and peptidomic analysis of cerebrospinal fluid (CSF). In the current study, we performed an in‐depth analysis of the human CSF endopeptidome to establish an inventory that may serve as a basis for future targeted biomarker studies. High‐pH RP HPLC was employed for off‐line sample prefractionation followed by low‐pH nano‐LC‐MS analysis. Different software programs and scoring algorithms for peptide identification were employed and compared. A total of 18 031 endogenous peptides were identified at a FDR of 1%, increasing the number of known endogenous CSF peptides 10‐fold compared to previous studies. The peptides were derived from 2 053 proteins of which more than 60 have been linked to neurodegeneration. Notably, among the findings were six peptides derived from microtubule‐associated protein tau, three of which span the diagnostically interesting threonine‐181 (Tau‐F isoform). Also, 213 peptides from amyloid precursor protein were identified, 58 of which were partially or completely within the sequence of amyloid β 1–40/42, as well as 109 peptides from apolipoprotein E, spanning sequences that discriminate between the E2/E3/E4 isoforms of the protein.